Integrasi Kearifan Lokal Berbasis Media Digital dalam Pembelajaran Menulis Teks Eksposisi: Studi Fenomenologi pada Siswa Sekolah Menengah Atas - Ridwan Syahputra; Rachel Yoan Katherin Putri Br. Siahaan; Mimi Rosadi; Maslan Sihombing; Aprili Yanti; Arini Vika Sari (Medan Resource Center, 2026)
Writing exposition texts remains a significant challenge for senior high school students, particularly in generating ideas, developing coherent arguments, and organizing texts systematically. This study investigates how the integration of local wisdom through digital media contributes to students’ learning experiences and writing development by addressing the following questions: how do students perceive the learning process, and how does this instructional approach support their exposition text writing? Employing a descriptive qualitative design, the study involved 25 senior high school students. Primary data were collected through classroom observations, semi-structured interviews, and documentation, while secondary data were obtained from relevant scholarly literature. The data were analyzed through data reduction, data display, and conclusion drawing, with source triangulation employed to enhance the credibility of the findings. The results demonstrate that integrating local wisdom with digital media facilitates idea generation, strengthens student engagement, and promotes a more contextual and meaningful learning experience. Nevertheless, many students continue to encounter difficulties in organizing arguments and maintaining coherent exposition text structures. The study concludes that this instructional approach provides a valuable pedagogical framework for enhancing exposition writing, although additional instructional support is required to improve students’ organizational and argumentative writing skills.